PTH-018 Is dysphagia under investigated at endoscopy?. (8th June 2018) - Chadwick, Georgina; Hoare, Jonathan
Abstract : Introduction: The 2015 NICE guidelines recommend endoscopy (OGD) to investigate dysphagia, to rule out oesophageal cancer. However when performing these endoscopies it is important to look for other causes of dysphagia like gastro oesophageal reflux disease (GORD) and rarer conditions such as eosinophilic oesophagitis (EOE). The recently published BSG quality standards for endoscopy suggest that biopsies should be taken from two different sites in the oesophagus to rule out eosinophilic oesophagitis in those presenting with dysphagia/food bolus obstruction, where an alternative cause is not found. This study aimed to investigate the proportion of patients who had biopsies at endoscopy performed for dysphagia, and look at other investigations performed and final diagnosis made. Methods: Using Scorpio all OGDs performed for dysphagia between Jan 2017 and March 2017 were identified. Primary outcome assessed was proportion of patient with dysphagia who had oesophageal biopsies performed, if no visible cause was found. Other outcomes assessed included biopsy findings, additional investigations performed and final diagnosis made. Results: 155 OGDs were performed for dysphagia, 76.7% were urgent referrals, mean (±SD) age of patient was 62.3 (±17.3) years. 108 (69.67%) patients had no visible cause for dysphagia identified at endoscopy, but only 55 (50.9%) of these patients had an oesophageal biopsy. Histology findings for these 48 cases are reported in table 1. 21 (19.4%) patients with no visible lesion had further investigation after endoscopy: 8 (7.4%) barium swallow, 9 (8.3%) CT and 3 (2.8%) manometry. Final diagnosis for all patients who had no structural lesion (6 months after initial OGD): 64 (59.3%) had no diagnosis, 26 (24.1%) had GORD, 5 (4.6%) had a dysmotility disorder, 4 (3.7%) had EoE and 6 (5.6%) had BE. Conclusion: Two thirds of patients had no visible cause of dysphagia identified at endoscopy, but only half of these patients had oesophageal biopsies taken as recommended by the BSG. Where there were taken the most common finding was normal histology (41.8%), while 40.0% had GORD and only 7.3% had EOE. Nearly 60% of patients with dysphagia who are referred for endoscopy have no formal diagnosis made 6 months after initial endoscopy.